TANGGUNG JAWAB NOTARIS DALAM PEMBUATAN AKTA PENGIKATAN HIBAH YANG DIBUAT ATAS DASAR PENYALAHGUNAAN KEADAAN (CONTOH KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 892 K/PDT/2017) - Joshua Tanaya; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2020)
Notary as a public official is authorized to make all kinds of authentic deeds, one of them is in terms of making agreements.In making agreements, Article 1320 Civil Code provides the general conditions by which a contract is valid. It consists of 4 (four) conditions, which if one of the conditions isn’t fulfilled it could cause certain legal consequences relating to the validity of the agreement. In Decision 892 K / Pdt / 2017 the grant binding agreement was made under misuse of circumstances, that caused a legal problem regarding the deed’s validity.In addition a notary public should take responsibility for the deeds.The result is that the grant binding agreement that was made under misuse of circumstances shall not be considered valid and is cancelled by the judges. In addition, notary’s responsibility upon his actions is that Notary may be sanctioned by civil sanctions in form of compensation, criminal sanctions in form of imprisonment and administrative sanctions.